China Coast Guard’s Water Cannon Use Against Philippine Vessels: UNCLOS Legality and Policy - M. Fabian Akbar; Hilmi Fattahuddhiyaa Putra Pramono; Laras Lingganingrum; Arif Reksa Pambudi; Ayesha binti Abul Hisyam (Fakultas Hukum Universitas Lampung, 2026)
This article examines whether the China Coast Guard's use of water cannons against Philippine vessels in the disputed South China Sea can be justified as a maritime law enforcement measure under the United Nations Convention on the Law of the Sea (UNCLOS). The analysis focuses on three legal issues: the legal status of the maritime area where the incident occurred, China’s jurisdictional basis to conduct law enforcement, and the compliance of water cannon use with the principles of necessity, proportionality, and due regard. This study uses a normative legal research method by analyzing UNCLOS provisions, the 2016 South China Sea Arbitration, and relevant international standards on the use of force in maritime law enforcement. The article argues that the legality of water cannon use cannot be assessed only from its non-lethal character. It must first be determined whether China had lawful jurisdiction over the area and the vessel concerned. If the incident occurred in an area where the Philippines holds sovereign rights under UNCLOS, or where China’s historic rights claim has no legal basis, China’s use of water cannons cannot be justified as lawful maritime enforcement. Such conduct may instead constitute coercive action that interferes with navigational rights, Philippine sovereign rights, and the duty of due regard. The article concludes that the use of water cannons in disputed maritime areas must meet strict requirements of necessity and proportionality, and any excessive or jurisdictionally unsupported use may give rise to international legal responsibility.